DNA nanoparticle-mediated thymulin gene therapy prevents airway remodeling in experimental allergic asthma - Da Silva, Adriana L. (2013)
Thymulin has been shown to present anti-inﬂammatory and anti-ﬁbrotic properties in experimental lung diseases. We hypothesized that a biologically active thymulin analog gene, methionine serum thymus factor, delivered by highly compacted DNA nanoparticles may prevent lung inﬂammation and remodeling in a mouse model of allergic asthma. The DNA nanoparticles are composed of a single molecule of plasmid DNA compacted with block copolymers of poly-L-lysine and polyethylene glycol (CK30PEG), which have been found safe in a human phase I/II clinical trial. Thymulin plasmids were detected in the lungs of ovalbumin-challenged asthmatic mice up to 27 days after administration of DNA nanoparticles carrying thymulin plasmids. A single dose of DNA nanoparticles carrying thymulin plasmids prevented lung inﬂammation, collagen deposition and smooth muscle hypertrophy in the lungs of a murine model of ovalbumin-challenged allergic asthma, leading to improved lung mechanics. In the present model of chronic allergic asthma, highly compacted DNA nanoparticles using thymulin analog gene modulated the inﬂammatory and remodeling processes improving lung mechanics.